Fatores associados à tensão do papel de cuidador em cuidadores informais de idosos - Dalla Vechia, Akeisa Dieli Ribeiro (2018)
Introduction: The role of caregiver strain (TPC) is difficult to play the role of caregiver in the family or other significant and affects many subjects involved in care to dependent persons. This is a multidimensional phenomenon that features physical and emotional state changes of caregiver, imbalance between activity and home and individual coping compromised. Objective: To analyze the factors associated with the nursing diagnosis caregiver role strain on informal careers of older people. Method: Transversal study and analytical realized with informal caregiver’s elderly registered in five main family health Strategies (ESF) in the North of the city of Cuiabá-MT. The study's sampling was probabilistic convenience type, not composed of 99 caregivers. The data were collected in the months of July to September 2017 through interviews using questionnaire validated with socio-demographic issues and to determine the diagnosis. In addition, we used the Mini Mental State examination (MMSE) to evaluate the cognitive ability of elderly/elderly caregivers, major depression inventory (MDI) for screening for depression in caregivers and Functional independence measurement (FIM) for check the degree of dependency of the elderly for the accomplishment of tasks. Descriptive analysis was performed with absolute and relative frequency and bivariate statistical analysis to check the possible associations through the Chi-square test (x2 ). Multivariate analysis was also carried out by multiple logistic regression to identify related factors associated with the TPC. The stepwise method forward for selection of variables for fitting the final model considering p<0,20 in bivariate analysis. Results: 98,0% of caregivers have TPC 74,2% being of type light/moderate and 25,8% of the serious type. The factors associated with the TPC were unpredictability of care situation (p<0,001), codependence of the elderly (p=0,002), elderly dependence (p=0,035) and instability of health of the elderly (p=0,023). Conclusion: The findings of this study identified the main related factors that are associated with the TPC. This points to the need for reorganization of the work of the teams of ESF units and the development of multidisciplinary evaluation and continuous the elderly and their families. The nurse should be able to establish the diagnosis TPC helping caregivers to choose the best strategies for providing care to the elderly, helping it to overcome the difficulties in the performance of your function.